Pickle water ameliorates castor oil-induced diarrhea in mice by regulating the homeostasis of the gut microbiota and intestinal mucosal barrier - Zhou, Tian; Long, Dongmei; Zhou, Maoting; Hu, Xianghong; Wang, Yu; Wang, Xing (Frontiers in Nutrition, 2024)
Introduction Diarrhea is a common clinical condition that can potentially be fatal. Current treatment options often have side effects, such as constipation and vomiting, and there remains a need for more effective therapies. Pickled vegetables, a famous traditional food in China, have been suggested in clinical studies to alleviate diarrhea in children, particularly through the use of pickle water (PW). However, the pharmacological effects and mechanisms of PW on intestinal health remain unclear. This study aimed to explore the protective effects of PW on castor oil-induced diarrhea in ICR mice and to investigate its potential mechanisms. Methods To evaluate the antidiarrheal effects of PW, we used a castor oil-induced diarrhea model in ICR mice. Various indices were measured to assess the severity of diarrhea. After euthanizing the mice, oxidative stress markers in the ileum were assessed using biochemical methods, and the expression of tight junction-related proteins in the ileum was analyzed using Western blot. Additionally, 16S rRNA high-throughput sequencing was used to evaluate the diversity and composition of the intestinal flora. Results The results showed that PW supplementation reduced body weight without significantly affecting organ index and liver function in the castor oil-induced diarrhea mice. PW also effectively reduced the dilution rate, diarrhea index, average loose stool grade, propelling distance of carbon powder, and intestinal propulsive rate while improving the pathological abnormality in the ileum. Furthermore, PW enhanced the activities of total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-PX), and catalase (CAT) while reducing malonaldehyde (MDA) levels. PW also increased the expression of tight junction proteins zonula occludens-1 (ZO-1) and occludin in the ileum. Additionally, the analysis of 16S rDNA revealed that PW increased both α and β diversity, improved the composition of the intestinal flora, and restored it to a normal level. Discussion Collectively, dietary PW administration ameliorates Castor oil-induced diarrhea by restoring tight junctions between intestinal mucosal cells, suppressing oxidative stress, and regulating the composition of intestinal flora. These findings suggest that PW may be a promising strategy for managing diarrhea.